Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd000376.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Longchain polyunsaturated fatty acid supplementation in infants born at term

Abstract: Long chain polyunsaturated fatty acid supplementation in infants born at term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
3
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 49 publications
2
39
3
1
Order By: Relevance
“…There is inconclusive evidence from randomized controlled clinical trials that LCPUFA supplementation of formula milk or supplementation of breastfeeding mothers improves neurodevelopmental outcomes of infants born at term. 32 , 33 In our cohort, however, the duration of child intake of fish was more predictive of BSID-III cognitive score at age 18 months than were nutrients received during the intrauterine period.…”
Section: Discussioncontrasting
confidence: 58%
“…There is inconclusive evidence from randomized controlled clinical trials that LCPUFA supplementation of formula milk or supplementation of breastfeeding mothers improves neurodevelopmental outcomes of infants born at term. 32 , 33 In our cohort, however, the duration of child intake of fish was more predictive of BSID-III cognitive score at age 18 months than were nutrients received during the intrauterine period.…”
Section: Discussioncontrasting
confidence: 58%
“…These anatomic observations have been supported by findings from animal and some human studies (Anderson GJ et al 2005; Anderson JW et al 1999; Brion et al 2011; Innis 2000; Kramer et al 2008). However, meta-analyses of randomized trials have not found evidence of persistent bene-ficial effects of LCPUFA supplementation of formula milk on the physical, visual, and neuro-develop-mental outcomes of term or pre-term infants (Simmer et al 2008a, 2008b). Limited evidence from randomized trials of fish oil supplements in pregnancy supports a cognitive bene-fit for offspring (Dunstan et al 2008), although other trials found no bene-ficial effects (Helland et al 2008; Makrides et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…A Cochrane review undertaken by Simmer et al (2008) included 11 studies and concluded that there is currently not enough evidence to support the supplementation of infant formulas with LCPUFA to benefit cognitive development in children born at term. Another review by McCann and Ames (2005) considered animal as well as human supplementation studies.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%